O plurilinguismo : um trunfo? - Pinto, Maria da Graça Lisboa Castro (2013)
The phenomenon of globalization and the ease with which people today circulate, virtually and personally, in the "global village" that is our planet, more than justifies the closer contacts among peoples and therefore among speakers of different languages, who are at the same time holders of the most diversified cultures. Bearing this setting in mind, this paper deals with some terms that are being used more frequently today (acquisition, learning, bilingualism, multilingualism, second language, foreign language, third language, plurilingualism), considers their coverage and draws attention to what each term may hide beyond its more obvious meaning. Based on an historical perspective, this paper also attempts to find an answer to the proposed title, using additional approaches from the cognitive domain, aimed at exploring and discussing a question that seems, at first sight, obvious and affirmative.